Spray coating of dense proton-conducting BaCe0.7Zr0.1Y0.2O3 electrolyte for low temperature solid oxide fuel cells - Fan, Liangdong (2017)
In this work, we report the spray coating, a simple and effective method, to prepare proton conducting BaCe0.7Zr0.1Y0.2O3 (BCZY) membranes on the pre-annealed porous anode substrates. The effects of sintering temperature on the electrolyte membrane and anode microstructure, proton conductivities of the resulted thin films, and their fuel cell performances in H2/air were investigated. Dense BCZY membranes with improved anode microstructure and good proton conductivity have been successfully obtained at reduced temperature using ZnO sintering aid. SOFCs using spray-coated electrolyte thin films gave a stable OCV value of 1.03 V and a maximum power density of 362 mW cm−2 at 650 °C when operated using hydrogen as fuel and air as the oxidant.